Development of Bright Fluorescent Poly(1-vinyl-2-pyrrolidone-co-acrylonitrile) and Its Polysalts with HCl and HNO3: Materials for Solid State Electrical Applications - Samiran Upadhyaya; Rajumani Sarma; Abdul Barik; Neelotpal Sen Sarma (Advances in Polymer Technology)
Herein, we have reported the synthesis, characterization, and ionic conductivity analysis of fluorescent poly(1-vinyl-2-pyrrolidone-co-acrylonitrile) and its salts with 10% HCl and HNO3 in solid state. The synthesized polymers and their polysalts were characterized using Fourier-transformed infrared spectroscopy, UV-visible, Cyclic Voltammetry, Thermogravimetric analysis, Differential Scanning Calorimetric, X-ray diffraction, and spectrofluorometric techniques. The AC conductivities were measured in the frequency ranging from 42 Hz to 1 MHz and temperature from 30°C to 70°C in solid state. Ionic conductivities of the salts of the copolymer with hydrochloric acid and nitric acid were found to be 2.145×10−5 and 2.349×10−5 S cm −1, respectively, which are nearly 1000 times more than that of poly(1-vinyl-2-pyrrolidone-co-acrylonitrile). The activation energies for the copolymer and the polyelectrolytes were found to be 0.454, 0.6288, and 0.659 eV, respectively. The transport number of the copolymers was found to be 0.0278, and that of the polysalts was found to be 0.7596 and 0.7424, respectively. The copolymer showed distinct fluorescent when irradiated with UV light and can be used as acid vapor sensor in solid state.